Pengaruh Kualitas Pelayanan dan Kepercayaan terhadap Loyalitas Konsumen dengan Kepuasan Pelanggan Sebagai Variabel Intervening - Taufik, Muhammad Taufik; Salim, Emil; Pratiwi, Nila (Jurnal Ekonomi & Bisnis, 2024)
Consumer loyalty is customer loyalty to a product or service, which is influenced by service quality and trust. Good service quality and high trust increase customer satisfaction. This satisfaction then becomes an intervening variable that strengthens the relationship between service quality, trust and consumer loyalty. This research aims to find out what influence Service Quality, Trust has on Consumer Loyalty and Customer Satisfaction as an Inteirveining Variable for Consumers at Caffei Kubik Koffiei Padang. The data collection method was through observation, interviews, questionnaires and documentation, with a sample of 100 respondents. The data analysis methods used are external model analysis, good quality of fit, descriptive analysis, and structural model testing using SmartPLS 3. The results of this research indicate that service quality has a positive and insignificant influence on customer satisfaction. Trust has a positive and significant influence on satisfaction. Service quality has a positive and significant influence on consumer loyalty. Trust has a negative and insignificant influence on consumer loyalty. Customer satisfaction has a positive and significant influence on consumer loyalty. Service quality cannot mediate customer satisfaction and consumer loyalty. Trust is able to mediate customer satisfaction regarding consumer loyalty to Caffei Kubik Koffiei Padang. This research provides insight for the management of Caffei Kubik Koffiei Padang regarding the importance of increasing customer trust and satisfaction to build consumer loyalty.